JOMEINO 2020
DOI: 10.31039/jomeino.2020.4.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Stock price reaction to dividend announcement: An empirical study on Dhaka Stock Exchange (DSE)

Abstract: The major objective of this study is to identify whether dividend announcement convey any information to the market that results a price reaction. With the objectives in mind, this paper used only secondary data from DSE. The study comprised a total of 21 companies these are listed by DSE. The research is only quantitative in nature. The empirical part of this study employs a standard 'event study methodology' to analyze the stock price reaction to dividend announcement. With the help of 'event study methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…It means EPS has a significant impact on the MVPS similar to the result found by Omokhudu and Ibadin (2015); 2018) but varying Ghosh and Ghosh (2015). The beta coefficient of CDPS and SDPS are 0.174 and 0.192, with a p-value of 0.946 and 0.990, respectively, which are statistically not significant varying Omokhudu and Ibadin (2015); Zahan and Rana (2020) and Olowolaju and Ogunsan (2017). Finally, it can be said that NOCFPS, NAVPS, and EPS have a significant impact, while CDPS and SDPS have no significant impact on the MVPS.…”
Section: Regression Analysismentioning
confidence: 50%
See 2 more Smart Citations
“…It means EPS has a significant impact on the MVPS similar to the result found by Omokhudu and Ibadin (2015); 2018) but varying Ghosh and Ghosh (2015). The beta coefficient of CDPS and SDPS are 0.174 and 0.192, with a p-value of 0.946 and 0.990, respectively, which are statistically not significant varying Omokhudu and Ibadin (2015); Zahan and Rana (2020) and Olowolaju and Ogunsan (2017). Finally, it can be said that NOCFPS, NAVPS, and EPS have a significant impact, while CDPS and SDPS have no significant impact on the MVPS.…”
Section: Regression Analysismentioning
confidence: 50%
“…(2018) but varying Ghosh and Ghosh (2015). The study also found that CDPS and SDPS were positively insignificantly correlated varying Omokhudu and Ibadin (2015); Zahan and Rana (2020) and Olowolaju and Ogunsan (2017). The NOCFPS, NAVPS, and EPS have a statistically significant impact on the MVPS.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this way, a few tests have been performed to discover whether the offer market responds fittingly with the declaration of significant data. Ahsan et al (2003) has directed one such examination on recorded protections in Dhaka Stock Exchange by fostering the accompanying invalid theory that "there is no huge distinction in share cost increment and decline previously, then after the fact the declaration of procuring." The test has been led at a 5% importance level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, these take time to learn the market. Moreover, it is hard to consider diverse parameters like cash bonus, dividends and earning per share in the learning state whereas bonus and dividend attract investors significantly [25,26] . Investor does not understand all issues related to a learning system.…”
Section: Introductionmentioning
confidence: 99%